Evaluation of viewing experiences induced by a curved three-dimensional display - Mun, Sungchul; Park, Min-Chul; Yano, Sumio (SPIE-SOC PHOTO-OPTICAL INSTRUMENTATION ENGINEERS, 2015)
Despite an increased need for three-dimensional (3-D) functionality in curved displays, comparisons pertinent to human factors between curved and flat panel 3-D displays have rarely been tested. This study compared stereoscopic 3-D viewing experiences induced by a curved display with those of a flat panel display by evaluating subjective and objective measures. Twenty-four participants took part in the experiments and viewed 3-D content with two different displays (flat and curved 3-D display) within a counterbalanced and within-subject design. For the 30-min viewing condition, a paired t-test showed significantly reduced P300 amplitudes, which were caused by engagement rather than cognitive fatigue, in the curved 3-D viewing condition compared to the flat 3-D viewing condition at P-3 and P-4. No significant differences in P300 amplitudes were observed for 60-min viewing. Subjective ratings of realness and engagement were also significantly higher in the curved 3-D viewing condition than in the flat 3-D viewing condition for 30-min viewing. Our findings support that curved 3-D displays can be effective for enhancing engagement among viewers based on specific viewing times and environments. (C) 2015 Society of Photo-Optical Instrumentation Engineers (SPIE)
Keywords: STEREOSCOPIC 3D; VISUAL FATIGUE; IMAGING-SYSTEM; LENS ARRAY; SUSCEPTIBILITY; CORTEX; SSVEP; ERP